Examining customer purchase decision towards battery electric vehicles in Vietnam market: A combination of self-interested and pro-environmental approach - Trong Truong Hoang; Thu Huong Pham; Thi Minh Hien Vu (Cogent Business & Management, 2022)
This research aims at examining determinants of battery electric vehicle (BEV) purchase in Vietnam market from both self-interested and pro-environmental perspectives. Data collected from 200 BEV drivers show that purchase intention is positively affected by self-interested factors such as performance expectancy, effort expectancy and facilitating conditions. Additionally, intention could be shaped by personal norm, which is influenced by awareness of consequences and ascription of responsibility. Finally, intention is a reliable predictor of purchase behavior, and the relationship is moderated by personal innovativeness. This research provides various theoretical and practical implications to enhance public acceptance towards BEVs.